FOSTERING SUSTAINABLE DEVELOPMENT GOALS THROUGH ENGLISH EDUCATION AT THE UNIVERSITY OF WORLD ECONOMY AND DIPLOMACY - Rikhsiyev, R (International Journal of Literature and Language Studies, 2026)
This paper is about the effectiveness of task-based activities that incorporated Sustainable Development Goals (SDGs) into the English language classes at the University of World Economy and Diplomacy (UWED). The main aim of these activities was to enable students to think critically and to research SDG-related issues. A survey was organized in order to learn about how effectively the task-based activities were implemented and to find out the impact on student learning. The paper also highlights the institution’s efforts to align English education with SDGs to increase student awareness of critical global issues and to assess the impact of task-based activities on students’ language proficiency.